Outcome of Orbital Complications of Acute Rhinosinusitis in Children (Iraqi Journal of Medical Sciences, 2021)
Background: Acute bacterial rhinosinusitis occurs commonly as a sequel to a viral upper respiratory tract infection. Spread of infection outside the sinuses to the surrounding brain and orbit results in complicated sinusitis. Complications are more common in children than adults due to anatomical and immunological factors. Objective: To identify the correlation of orbital manifestations with computed tomography (CT) scan findings in diagnosing and classifying the disease, the efficacy of various treatment modalities and the outcome of these complications in children.Methods: A prospective study of 16 patients who presented with orbital swelling and features of acute rhinosinusitis was conducted in the Otorhinolaryngology Department at Al-Imamein Al-Kadhimein Medical City from April 2014 to October 2015. A full history, ear, nose and throat (ENT) examination including naso-endoscopic examination (if possible), ophthalmological assessment and CT scan of nose and paranasal sinuses were done. Patients were classified to have either pre-or postseptal infection depending on CT findings. All patients were admitted to the ENT ward, received intravenous broad-spectrum antibiotics and supportive measures and kept under close observation with monitoring of ophthalmological manifestations and vital signs. Some patients responded to medical treatment and others required surgical intervention. All patients after recovery were discharged home on oral antibiotics for 2 weeks and followed up monthly for a total duration of 3 months.Results: The majority of patients were males (62.5%). Mean ages of patients was 8.9±2.9 years with a range (4 to 15) year. Preseptal cellulitis was more common (62.5% vs. 37.5%). Impaired visual acuity, impaired extraocular movement and proptosis were significantly associated with postseptal infections as the P values were 0.01, 0.003 and 0.003 respectively. Preseptal cellulitis responded well to medical treatment. Postseptal abscesses required surgical drainage using an external, endoscopic or combined approach. 94% of patients had complete recovery without any sequel.Conclusion: Orbital manifestations are strongly correlated with CT findings. Medical treatment is very effective for preseptal infection. The choice of surgical approach for managing postseptal infection will depend upon, the site and extension of the abscess and the state of the nasal cavity. Early and accurate management can reduce morbidity and mortality.Keywords: Orbital complications of sinusitis, pediatric rhinosinusitis, ethmoiditisCitation: Al-Hassani JMK. outcome of orbital complications of acute rhinosinusitis in children. Iraqi JMS. 2021; 19(1): 90-98. doi: 10.22578/IJMS.19.1.12
Keywords: Orbital complications of sinusitis; pediatric rhinosinusitis; ethmoiditis